Case Report: Administration of Amniotic Fluid-Derived Nanoparticles in Three Severely Ill COVID-19 Patients - Mitrani, Maria Ines; Bellio, Michael A.; Sagel, Anthony; Saylor, Marie; Kapp, William; VanOsdol, Kathryn; Haskell, Gwendolyn; Stewart, Danique; Abdullah, Zanub; Santos, Ivan; Milberg, Julian; Arango, Alissa; et al. (Frontiers in Medicine, 2021)
Rationale/Objectives: A human coronavirus (HCoV-19) has caused the novel coronavirus disease (COVID-19) outbreak worldwide. There is an urgent need to develop new interventions to suppress the excessive immune response, protect alveolar function, and reduce lung and systemic organ damage. Organicell Flow is a novel therapeutic that is derived from the soluble and nanoparticle fraction of human amniotic fluid. Here within, we present the clinical outcomes of three critically ill patients suffering from COVID-19 infection treated with Organicell Flow. All patients were hospitalized greater than 35 days in the ICU and approved by the FDA for eIND use. Methods: Organicell Flow was administered to patients with standard of care and followed for 28-days post therapy. SOFA score assessment, chest X-Rays, and inflammatory biomarker testing was performed. Main Results: All compassionate use patients showed improvements in ICU clinical status and experienced respiratory improvements. Acute delirium experienced by patients completely resolved, inflammatory biomarkers improved and there are no detectable adverse effects. Conclusions: This is the first demonstration of human amniotic fluid-derived nanoparticles as a safe and potentially efficacious therapeutic treatment for respiratory failure induced by COVID-19 infection.